Sex-specific spirometry effects of adult COPD polygenic score in children with asthma - Jelte Kelchtermans; Joseph M. Collaco; Huiqi Qu; Frank Mentch; Sharon A. McGrath-Morrow; Hakon Hakonarson (Scientific Reports)
Abstract Chronic obstructive pulmonary disease (COPD) is a leading cause of death and disability globally. While genetic and environmental risk factors are known, these insights have not yet resulted in individualized prevention strategies. Polygenic scores (PS) have enhanced our understanding of genetic risk and early-life lung function differences, but their applicability across diverse populations remains unclear. As such, we aimed evaluate whether a COPD PS captures population-wide risk or disproportionately affects sub-populations defined by ancestry or sex. This observational study assessed the association between a previously validated COPD PS and lung function in children with asthma, using spirometry results from children with asthma in the Center of Applied Genomics biorepository. Mixed-effects linear regression models were used to examine the relationship between PS and spirometry measures (FEV1 and FEV1/FVC), with stratified analyses by sex and ancestry. 25,477 spirometry results from 6336 patients were included. Population-wide, children in the high PS group had significantly lower FEV1/FVC z-scores compared to the low PS group (P = 0.0037, beta =  − 0.11, 95% confidence interval [CI] − 0.18 to − 0.036). When stratified by sex, high PS was associated with lower FEV1/FVC z-scores in males (P = 0.0088, beta =  − 0.14, 95% CI − 0.24 to − 0.035), but no significant effect was found in females. Ancestry-specific analysis revealed that males of European (EUR) ancestry with high PS had significantly lower FEV1 (P = 0.0035, beta =  − 0.37, 95% CI − 0.63 to − 0.12) and FEV1/FVC z-scores (P = 0.00076, beta =  − 0.35, 95% CI − 0.55 to − 0.15). No significant associations were observed in females with EUR ancestry or in African ancestry groups. Logistic regression analysis showed that high PS in males of EUR ancestry increased the odds of having an FEV1/FVC ratio below 0.7, a marker for COPD (P = 0.0074, OR = 2.01, 95% CI 1.19 to 3.31). This study demonstrates sex-specific effects of a COPD PS in pediatric asthma patients, with males of EUR ancestry at highest risk. The findings underscore the need to include diverse populations in genomic studies to improve the generalizability of PS for COPD prevention.